Research Methodology Textbook for ELT Students based on A Gen-Z Learning Style - Ega Nur Fadillah (Journal of World Science, 2026)
The research aims to identify the learning needs of Gen-Z students regarding research methodology and to develop a contextualized Research Methodology Textbook tailored to their characteristics and ELT practices. This study addresses this gap by the challenges faced by English Education students in comprehending research methodology, which are largely due to the overly theoretical and textual nature of existing textbooks. Using a Research and Development (R&D) design guided by the ADDIE model, the study involved 20 fifth-semester students and 3 lecturers from the English Language Teaching Department at 5 universities at Cirebon, West Java, Indonesia. Data were collected through questionnaires, semi-structured interviews, focus group discussions, classroom observations, and expert validation checklists. Quantitative analysis showed that students’ confidence in understanding research methodology was relatively low (M = 2.8), suggesting that methodological concepts remain challenging when presented through conventional textbooks. Lecturers’ slightly higher rating (M = 3.2) reflects their awareness of these difficulties and highlights the urgent need for contextualized learning resources tailored to English Education students. Qualitative findings revealed that Qualitative insights reinforce the quantitative results, showing that the primary barrier to students’ mastery of research methodology is the theoretical and text-heavy structure of existing textbooks. Students frequently reported that traditional explanations feel abstract and disconnected from their experiences as future English teachers. These findings suggest that research methodology learning materials be redesigned to include visual, interactive, and ELT-contextualized components, supported by step-by-step scaffolding to address Gen-Z learners’ difficulties with theoretical explanations.